The blessings and curses of C57BL/6 substrains in mouse genetic studies - Bryant, Camron D. (Ann N Y Acad Sci, 2011)
Phenotypic and genetic differences among C57BL/6 substrains are accumulating. Investigators must address these differences to improve the quality of their studies.